Rights of Alleged Victims in Penal Proceedings Provisions in Canon Law and the Criminal Law of Different Legal Systems - Scicluna, Charles J.; Wijlens, Myriam (Edition Seehaus [plus] - Resozialisierung - Opferschutz - Restorative Justice, 2023)
The rights of victims of sexual abuse as minors in penal proceedings is gaining increasing attention. International standards have been developed and national judicial systems have implemented them and developed them further. This book presents the standards, the provisions of nine different countries as well as four studies suggesting possible improvements to the role of victims in the canonical penal proceedings of the Roman Catholic Church. This unique collection of studies, written by leading authorities in the field of rights of victims of sexual abuse as minors in the civil realm, offers fascinating proposals by outstanding canon lawyers for improvements to the penal procedural law of the Roman Catholic Church. With contributions by Mark L. Bartchak | Jorge Cardona Llorens| Nicholas Cowdery | María Inés Franck | Jane Goodman-Delahunty | Aidan McGrath | Mary Graw Leary | Ma. Liza Miscala Jorda | Gianpaolo Montini | Raphaële Parizot | Livia Pomodoro | Frauke Rostalski | Fabián Salvioli | Charles J. Scicluna | Malgorzata Skorzewska-Amberg | Myriam Wijlens